Optimum light weight concrete mix design against high temperature - M.Q. Panahy; H. Ostadhossein; A. Mirzaii; A.H. Baghbani (مهندسی عمران شریف, 2022)
The fire phenomenon can cause the loss of structural materials resistance which may end to damage or even structural total collapse. Physical and chemical changes in concrete due to firing also make serious structural defects in concrete structures. Therefore, prevention of reduction of concrete resistance is attended in this research. The primary idea is based on decreasing concrete thermal conductivity to increase chemical and physical resistance. Because of low density and porosity light weight aggregate concrete has low thermal conductivity which can postpone the resistant loss due to high temperature. A set of tests performed to achieve an optimum light weight aggregate concrete mix design in room normal temperature by changing the amount of sensitive mix components and controlling compressive strength and density. In next step some effective additives were implemented to make the optimum mix design against high temperature. For this purpose, 9 different mix designs obtained from the Taguchi method were prepared. For each mix design, 9 test specimens were made. At each, ambient temperature, 400 ͦC and 800 ͦC, three samples of each design are tested. The experiments conducted in this research include testing of compressive strength, ultrasonic pulse, and weight loss and heat effect on the appearance of lightweight concrete. It was seen that the effect of temperature above 400 ͦC is more significant on concrete compressive strength and in temperatures below 400 ͦC density loss is more considerable. The results of tests indicate that reducing the water to cement ratio and using super plasticizer has a desirable effect on the physical and mechanical properties of lightweight concrete at higher temperatures. However, test results showed that the presence of silica fume up to 15 percent of weight of cement can’t improve the strength of lightweight concrete neither in ambient nor in elevated temperature. Optimum mix design lost about 49 percent of compressive strength in 800 ͦC. Also it was observed that loss of density and compressive strength due to elevated temperature are in direct relation.